NORMS, IDENTITY AND INDONESIA’S RESPONSES TO THE MYANMAR CONFLICT : A CONSTRUCTIVIST APPROACH TO FOREIGN POLICE - Azizah, Hikmatul; Fortuna, Jeny; Najuba, Viki Zulva; Masadi, Anwar (Spektrum, 2024)
This research aims to provide information related to Indonesia's norms, identity and response to the Myanmar conflict. The discussion will focus on the causes and role of Indonesia. Indonesia has an interest in this conflict, apart from the 1945 Constitution in maintaining world peace, the issue of this conflict is also within the Southeast Asian region which if not resolved quickly will affect regional security. The problem of Rohingya refugees in surrounding countries will become a new problem for the region, including Indonesia. The number of Rohingyas killed and displaced due to this conflict until 2019 has always shown a significant increase. This research uses a descriptive qualitative research model approach based on constructivism theory in analyzing problems empirically. . This theory emphasizes that state identity is shaped by values and norms that exist in structural (international norms) and subsystemic (local norms) areas.  The qualitative approach used in this research is a type of literature study whose data sources are analyzed from books and journals related to research on the Indonesian government's diplomacy efforts in mediating humanitarian conflicts in Myanmar. The findings of this study indicate that Indonesia through its diplomatic relations will not remain silent to see this conflict drag on.Keywords: Indonesian Response, Myanmar Conflict, Constructivism, Diplomacy